2015
DOI: 10.1111/pcn.12362
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of oxidative metabolism and oxidative DNA damage in patients with obsessive–compulsive disorder

Abstract: Aims: There are limited published data about the role of oxidative stress in the pathophysiology of obsessive-compulsive disorder (OCD). In addition, oxidative stress and oxidative DNA damage have not been investigated together in OCD. In this study, we aimed to evaluate oxidative stress and oxidative DNA damage in patients with OCD.Methods: Forty-two patients with OCD who were diagnosed in the Psychiatry Clinic of Gaziantep University and 38 healthy volunteers were enrolled in the study. Serum 8-hydroxideoxig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 28 publications
(75 reference statements)
0
19
0
Order By: Relevance
“…From full‐text review of the resulting 31 papers, 14 did not meet inclusion criteria and 17 were included in our qualitative synthesis. Four of these were ineligible for quantitative synthesis, resulting in 13 studies considered for quantitative analysis . Two of these studies assessed the same sample, but data from both were included since they provided complementary information (i.e., distinct markers and correlation between TBARS and Y‐BOCS) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From full‐text review of the resulting 31 papers, 14 did not meet inclusion criteria and 17 were included in our qualitative synthesis. Four of these were ineligible for quantitative synthesis, resulting in 13 studies considered for quantitative analysis . Two of these studies assessed the same sample, but data from both were included since they provided complementary information (i.e., distinct markers and correlation between TBARS and Y‐BOCS) .…”
Section: Resultsmentioning
confidence: 99%
“…Growing evidence supports the possibility that psychiatric disorders may be considered multisystem disorders, with patients presenting altered immune and oxidative markers, when compared to healthy controls . Specifically for OCD, while its exact etiology and pathophysiology remain unknown, systemic dysregulation of inflammation and oxidative stress has been increasingly reported . Regarding inflammation, recent meta‐analyses have confirmed that patients with OCD have reduced plasma IL‐1β and increased anti‐basal ganglia antibodies, in comparison with healthy controls .…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies have consistently provided support for a deficient glutathione oxidative protective system in the animal model of OCD, especially in the frontal cortex . The beneficial effect of minocycline in OCD patients is partly due to its anti‐oxidative characteristics, as oxidative stress is known to be associated with OCD …”
Section: Discussionmentioning
confidence: 99%
“…[ 6 , 7 ] Oxidative stress and reduced antioxidant status are common to many psychiatric disorders inclusive of schizophrenia, depression, bipolar, and obsessive-compulsive disorders. [ 1 , 8 ] Increasing production of glutathione assists in the restoration of redox imbalance in these conditions.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%